UPAYA PENGUATAN KELEMBAGAAN DESA DALAM MENCAPAI DESA ADHIKARYA PANGAN NUSANTARA TAHUN 2015 (Studi Kasus Desa Seberang Taluk Kecamatan Kuantan Tengah Kabupaten Kuantan Singingi) - Padri "; Baskoro Wicaksono (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Adhikarya Pangan Nusantara rewards the overwhelming contribution to encourage participation and creativity, and builds synergy between governments and communities in an effort to achieve sovereignty, independence, and food security. By certain criteria, this award is a form of government appreciation to institutions, communities, individuals, as well as agencies. The seberang taluk village is one of the villages that have yielded apprasement Adhikarya Pangan Nusantara in 2015. The problemof this research is how to build institutions in villages in reaching the village of Adhikarya Pangan Nusantara in 2015?? And what are the supporting factors of the village in reaching the Adhikarya Pangan Nusantara Villages? This research is descriptive research with qualitative approach. Location of this research in Seberang Taluk village. Datagathering techniques are done with qualitative data analysis.Meanwhile, the results of this study may be concluded that efforts in strengthening the institutional villages to reach the Adhikarya Pangan Nusantara villages ran optimally. Judging from the five indicators of institutional strengthening, growing community concern and building partnership. Moreover, in the indicator effort to build organizations, build up well planned system.And notice that each process of institutional development has run optimally And found no significant problems. However, the underlying factors are influencing the development of village institutions in reaching Adhikarya Pangan Nusantara village there are both internal and external factors. The internal factors is high commitment of headman and the available of budget. When, the external factors is partnerships with private parties. Key word: village institusional, Village, capacity